The elements of job evaluation in the development of a pay structural comparison system guide to conducting compensation surveys to determine competitive adjustments to base salary ranges - Snelgar, Robin John (Rhodes University, Faculty of Humanities, Department of Psychology, 1981)
If the wage policy of an organisation is to remain competitive in the labour market, that is, pay rates that are at least approximately equal to those prevailing in the community, then it must collect accurate wage and salary data in order to alter its pay structure as may become necessary. Wage and salary survey information provides a means by which management can determine whether its entire wage level is in accordance with that of the external labour market, and thus it is absolutely essential that methods and techniques utilised to collect such information are as objective and accurate as possible. The vital factor which has been revealed by the utilisation of many existing wage and salary survey guides is that the unavoidable subjectivity involved in the basic techniques utilised in survey procedures tends to have a cumulative effect on both data collection and analysis, and ultimately interpretation. As each technique is utilised, whether it be to obtain job comparability or to adjust salary data, the overall level of subjectivity is increased, which results in a cumulative increase in the margin of error involved in data collection. This study has been aimed at developing and practically testing a comprehensive guide to conducting wage and salary surveys which effectively minimises and, over successive surveys, eradicates the necessity for these subjective techniques. Due to the fact that the elements of job evaluation, namely, job analysis, job description, job specification and the job evaluation plan itself, form the nucleus of the techniques utilised for the data gathering and analysis process, the initial study was aimed at developing a job evaluation process which would be as objective as possible. In the development of such a system a range of job evaluation plans were tested for comparability in rating of jobs, the hypothesis being that any evaluation method or plan, when correctly applied to a series of jobs, will result in the same classification. This study intercorrelated rates derived for twenty-four key jobs selected from one particular organisation, using the job evaluation methods utilised by sixteen different organisations, and found that these rates intercorrelated between 0,93 to 0,99. These intercorrelations indicate a high degree of commonality among the sixteen methods; thus providing a justification for the utilisation of one particular job evaluation plan for the adjustment and weighing of wage and salary data in the survey data analysis procedure. To further justify the utilisation of one particular method, and thereby increase probability of acceptance by participating organisations, the independence of the sub-factors of the selected plan were tested by intercorrelating the factor scores for two job samples, one consisting of sixty jobs, type and level being heterogeneous, the other consisting of forty jobs, type and level being homogeneous. Sub-factor intercorrelations in the group of heterogeneous jobs ranged from 0,71 to 0,98 while all but one correlated at or above 0,90 with the total score, thus emphasising the independence of sub-factors, while intercorrelations in the group of homogeneous sample were much lower, ranging from 0,26 to 0,89, indicating greater factorial independence due to the fact that these jobs are limited to a narrower range of grades such that specific job differences in respect of sub-factors are more likely to show up. Utilising this selected job evaluation plan as the core of the developed job evaluation process, a wage and salary survey guide was formulated, the unique concept being a comparison of participating organisation pay structures rather than comparison of positions as a basis for data collection. The job evaluation system was utilised in the formulation of a "one-time" standardisation of participating organisation pay structures according to the survey organisation pay structure, the hypothesis being that these standardised pay structures may be utilised over successive surveys without the necessity for restandardisation, and thus eliminating the use of subjective methods and techniques subsequent to the initial standardisation. Utilising an international oil company as the survey organisation this newly formulated structural comparison guide was practically tested by applying it in conjunction with the existing survey organisation wage and salary survey guide as a means of competitive market wage and salary data gathering and analysis, over successive survey years, namely, 1974, 1977, and 1980. The results obtained through application of this guide were subsequently compared with those results obtained by two professional survey organisations, and proved to be reliable and consistent enough over the applicable survey years to warrant acceptance of the pay structural comparison concept as a valid wage and salary survey technique.
Keywords: Wage surveys; Job evaluation; Job analysis